Improving Teachers’ Digital Literacy Competence through Cap Cut-Based Instructional Video Production at SMA Negeri 1 Banyuasin - Nova Yanti Maleha; Juanisa Iriani; Cindi Pramita (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The rapid development of digital technology requires teachers to enhance their digital literacy competencies, particularly in developing interactive learning media. However, many teachers still have limited skills in producing video-based instructional materials. This study aimed to analyze the effectiveness of CapCut-based instructional video training in improving teachers’ digital literacy competencies at SMA Negeri 1 Banyuasin. The study employed a quantitative approach using a pre-experimental one-group pretest–posttest design involving 25 teachers. Data were collected through a digital literacy competency questionnaire using a five-point Likert scale and analyzed using paired sample t-test. The results showed a significant improvement in teachers’ competencies after the training. The mean score of understanding increased from 1.71 to 4.53 (increase = 2.82), while the mean score of interest increased from 1.74 to 4.37 (increase = 2.63). These findings indicate that hands-on, structured training effectively enhances both technical mastery and positive attitudes toward technology integration in learning. In conclusion, CapCut-based training contributes significantly to strengthening teachers’ digital literacy and supports pedagogical transformation in secondary education. The findings highlight the importance of experiential training models as a practical strategy for sustainable digital competence development in schools.